Improving student's learning outcomes through e-service learning based on authentic learning strategy - Atan, Noor Azean (Innovative Teaching and Learning Journal (ITLJ), 2018)
Student Learning Outcomes are statements that determine what the students know, can do or can demonstrate when they have completed or participated in a course. In order to achieve optimum student learning outcomes in a course at Higher Education Institutions, assessments should be conducted in a meaningful and authentic learning environment, such as service learning. However, for courses involving students from various faculties and across-discipline, they need a technology as a medium for better cooperations in the process of teaching and learning. Therefore, the purpose of this study was to examine the effects of online platform use in the service-learning programme, based on an authentic learning strategy towards Student Learning Outcomes (SLOs). A quantitative research design was used to conduct this research, involving 30 undergraduate students from different faculties who enrolled in one of the co-curriculum courses. The data analysis involved a pre-post-test in learning activities score. An analysis of Student Learning Outcomes (CLO1, CLO2, and CLO3) through a series of service learning activities in an online platform, based on authentic learning, showed an increment in the students' scores. Thus, this study concluded that integrating e-Service Learning in an authentic environment provides a further enhancement of Student Learning Outcomes.